2014
DOI: 10.1097/yco.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Innovative strategies for closing the mental health treatment gap globally

Abstract: The strategies outlined in this review hold great potential for enhancing mental health treatment services, and address some of the major barriers globally to accessing mental healthcare, such as scarcity of resources (infrastructure, capacity, and funding) and stigma. Despite much evidence supporting the efficacy of these models, thorough studies that test their feasibility, acceptability, utility, and effectiveness in various contexts, including low-income and middle-income countries, are required. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 53 publications
(40 reference statements)
0
71
0
6
Order By: Relevance
“…Another challenge in the organizational adoption is the technology itself, since not all facilities are equipped with modern devices or technological expertise [6]. Mobile technology with audio and video content that requires a good-quality device has been particularly challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another challenge in the organizational adoption is the technology itself, since not all facilities are equipped with modern devices or technological expertise [6]. Mobile technology with audio and video content that requires a good-quality device has been particularly challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Online and mobile tools can reach large populations and lower the barrier for seeking help [6,13,14]. RCT studies of technology-aided treatments for depression have shown their efficacy and effectiveness among diverse populations, especially when the treatments are professionally supported [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] The World Heart Federation's Roadmap has emphasised the "'treatment effectiveness cascade' from the cardiovascular event to the long-term adherence with priority interventions". 12 This systematic review illustrates that, particularly in low-income settings, the understanding of health system barriers and facilitators is poor from a research perspective, and that practical research and pragmatic solutions are urgently required, if the World Heart Federation's goals of reducing premature CVD mortality by at least 25% by 2025 are to be fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, a disturbingly high gap exists between the prevalence of those with mental disorders and those who receive treatment, particularly in low middleincome countries. It emerged that only about 35% to 50% of all subjects with mental disorders receive any professional help for their health [6]. Moreover, even once provided, there is often a notable treatment delay.…”
Section: Clinical Relevance and Impact Of Delayed Treatmentmentioning
confidence: 99%